Phonembewusstheit von Logopädie-Studierenden und -Auszubildenden - Digel, Mareike; Berendes, Karin; van Ermingen-Marbach, Muna; Heim, Stefan (Sprache · Stimme · Gehör, 2025)
To plan and carry out therapy effectively, speech therapists must have a high level of phonemic awareness in many disorders and be able to recognize orthographic interference effects. We assessed phonemic awareness at the beginning of the speech therapy study program (n = 116) and it is rather low with 39,5 % of correctly solved items. The operations tested (identifying, segmenting, manipulating) differ significantly, which suggests practicing the difficult operations during the study program.
Keywords: Phonembewusstheit; phonologische Bewusstheit; Logopädie-Studierende; Logopädie-Auszubildende; orthografische Interferenzeffekte